Effects of taurine on growth performance, body composition and physiological responses of western white shrimp, Litopenaeus vannamei broodstock - Vahid Morshedi; Mahmoud Nafisi Bahabadi; Mansour Torfi Mozanzadeh; Amin Oujifard; Naser Agh; Khalegh Maneii; Ahmad Qasemi; Nehzat Bakhshi; Hadi Ebrahimi; Rezvan Tamadoni; Shirin Hamedi; Reza Bagherpour; et al. (تغذیه آبزیان)
Introduction: The white shrimp, Litopenaeus vannamei has become a popular species for aquaculture worldwide due to its euryhaline nature and commercial importance. In aquaculture, the balance of nutrients in the diet of aquatic animals guarantees optimal growth and health improvement. Taurine (Tau = 2-aminoethanesulfonic acid) is an amino sulfonic acid, which has been proven to be conditionally essential for some aquatic animals when these animals are fed with diets containing high plant protein levels, due to taurine deficiency in plant-based protein sources. Tau has been also implicated in osmoregulation, modulation of neurotransmitters, hormone release, and antioxidation. Materials and Methods: A 30-day feeding study was conducted to determine the effects of supplementing the Tau in the diet of broodstock western white shrimp. Hawaiian domesticated shrimp stocks were transferred to Aquatic Research Laboratory, Persian Gulf University, from a private greenhouse pond (Delvar, Bushehr, Iran). Shrimp broodstock were disinfected with formalin (100 ppm, 30 s). Following two weeks of acclimatization to the husbandry system, the shrimp broodstock were placed in two 4000-L circular fiberglass tanks. A total of 180 shrimp broodstock with mean initial weight of 30.37 ± 2.36 g, were stocked into 18 black circular polyethylene tanks with a capacity of 250 L. Six isonitrogenous and isolipidic diets were supplemented with graded amounts of Tau including 0 (control), 2, 4, 6, 8, and 10 g/kg (T2, T4, T6, T8 and T10 respectively). To evaluate the effects of Tau on growth, body composition, digestive enzymes, and haemolymph biochemical parameters, sampling was taken at the end of the experiment. Results and discussion: The results showed that final weight, specific growth rate, weight gain, condition factor, and survival of shrimp fed with the supplemented diets with Tau had no significant differences than the control group (p>0.05). The protein content in the shrimp muscle of T6 was higher than T4 and the control group (p<0.05). The obtained results showed that hyaline cells in the haemolymph of T10 upraised, while semi-granular rate (%) decreased compared to the control group (p<0.05). However, other haemolymph indices and metabolites in the treatments fed with Tau-supplemented diets did not show significant differences compared to the control group (p>0.05). The present results showed that lipase activity upraised by increasing Tau levels in the treatments (p<0.05). The results show that the growth performance of broodstock was not influenced by dietary Tau during the shrimp maturation process. It may be attributed to the preference of the broodstock shrimp for gonadal growth rather than for somatic growth. Conclusion: The obtained results indicated that supplementing the broodstock diet with 6-10 g/kg Tau has beneficial effects on the protein content in the muscle and haemolymph biochemical indices, especially hemocyte cells and digestive enzyme activities of white shrimp broodstock during the maturation process.